EXAMPLES OF NATIONAL MUSIC OF THE UZBEK PEOPLE (Multidisciplinary Journal of Science and Technology, 2024)
Professional folk music created by musicians and singers over the centuries shows that the musical culture of the Uzbek people has a centuries-old history. The national music works of the ancestors of the Uzbek people are strongly connected with the creativity of the brotherly peoples who lived in the territory of Central Asia, first of all, the Tajik people[1].